New Insights Into c.815_824dup Pathogenic Variant of BRCA1 in Inherited Breast Cancer: A Founder Mutation of West African Origin - Diop, Jean Pascal Demba; Sène, Andréa Régina Gnilane; Dia, Yacouba; Ba, Seydi Abdoul; Mbacke, Serigne Saliou; Ly, Cheikh Ameth Tidiane; Sarr, Pierre Diaga; Diouf, Doudou; Ka, Sidy; Mbengue, Babacar; Gueye, Serigne Modou Kane; Diop, Pape Saloum; et al. (Frontiers in Oncology, 2022)
Founder mutations have been reported in BRCA1 and BCRA2 in different ethnic groups with inherited breast cancer. Testing of targeted mutations in specific population is important for cancer prevention in mutation careers. In Sub-Saharan Africa, few studies have reported specific founder mutations in inherited breast cancer. The pathogenic variant c.815_824dup of BRCA1 has been reported as the most frequent in African American population and was suggested to have a West African origin. Recent report from Senegal identified this variant in women with inherited breast cancer with the highest frequency never reported. The variant was linked to a common haplotype confirming its founder effect in West Africa. In this article we reviewed c.815_824dup mutation history and discuss how it spread out of Africa through transatlantic slave trade.